61.9k views
1 vote
2(× - 2)=4× - 6(× - 2)​

2 Answers

5 votes

[ Answer ]


\boxed{\bold{X \ = \ 4}}

[ Explanation ]

  • Solve:
    \bold{2(x - 2) = 4x - 6(x - 2)}

----------------------------------

  • [Expand]
    \bold{-6(x - 2): -6x + 12}

2x - 4 = 4x - 6x + 12

  • [Add Similar Elements]
    \bold{4x \ - \ 6x \ = \ -2x}

2x - 4 = -2x + 12

  • [Expand]
    \bold{2(x \ - \ 2): \ 2x \ - \ 4}

2x - 4 = -2x + 12

  • Add 4 To Both Sides

2x - 4 + 4 = -2x + 12 + 4

  • Simplify

2x = -2x + 16

  • Add 2x To Both Sides

2x + 2x = -2x + 16 + 2x

  • Simplify

4x = 16

  • Divide Both Sides By 4


(4x)/(4) =
(16)/(4)

  • Simplify

X = 4


\boxed{\boxed{\bold{[] \ Eclipsed \ []}}}

User Evgnomon
by
5.6k points
2 votes

Hey there!

Assuming you meant: "
\bold{2(x-2=4x-6(x-2)}"

If so follow these steps


  • \bold{Distribute\downarrow}

  • \bold{2(x)+2(-2)=4(x)+(-6)x+(-6))(-2)}

  • \bold{2(x)=2x}

  • \bold{2(-2)=-4}

  • \bold{4x=4x}

  • \bold{-6(x)=-6x}

  • \bold{(-6)(-2)=12}
  • We get:
    \bold{2x-4=(4x+(-6x))+12}[/tex</strong></li><li><strong>[tex]\bold{Combine\downarrow}
  • All the x-values are one and the regular numbers are one
  • We get:
    \bold{2x-4=-2x+12}

  • \bold{Add} by
    \bold{2x} on your sides

  • \bold{2x-4+2x=-2x+12+4}
  • We now get:
    \bold{4x-4=12}

  • \bold{Add} by
    \bold{4} on each of your sides

  • \bold{4x-4+4=12+4}
  • We get:
    \bold{4x=16}

  • \bold{Divide} by
    \bold{4} on each of your sides

  • \bold{(4x)/(4)=(16)/(4)}

  • \boxed{\boxed{\bold{Answer:x=4}}}\checkmark

Good luck on your assignment and enjoy your day

~
\frak{LoveYourselfFirst:)}

User Ramiro
by
5.6k points